A NOTE ON SOME MODELS OF INTUITIONISTIC FUZZY SETS IN REAL LIFE SITUATIONS - Ejegwa, P. A. (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
After the introduction of intuitionistic fuzzy sets (IFSs), many researchers have confirmed the resourcefulness of IFSs in decision making problems. In this paper, we gave a lucid and comprehensive note on some selected models of IFSs in real life situations such as in diagnostic medicine, career determination, and pattern recognition using normalized Hamming distance measure. Keywords: career determination, diagnostic medicine, intuitionistic fuzzy sets, pattern recognition.